Svět pro děti do tří let Vhledy do současné podoby rané výchovy a péče v ČR - Grůzová, Lucie (Masaryk University Press, 2022)
Title in English: A World for Children Under Three: Insights into the Current Form of Early Childhood Education and Care in the CR The book "A World for Children Under Three. Insights Into the Current Form of ECEC in the CR" is the first pedagogical-sociological book in the CR dealing with current facilities for children under three years of age - children's groups / micro-creches, kindergarten classes for two-year-olds, and children's centres. It is addressed to professionals, students, parents and everyone else interested in bringing the worlds of parents, caregivers and children who meet in these facilities closer together. It presents key research findings of the project ECEC in Day Care Facilities in the CR, relating to children's collective everyday life, the work of (head) teachers and nannies, and the experiences and expectations of parents, and relates them to the current system framework.